2006
DOI: 10.1097/01.hjr.0000194420.62379.de
|View full text |Cite
|
Sign up to set email alerts
|

Increased absenteeism from work among aware and treated hypertensive and hypercholesterolaemic patients

Abstract: Without being able to test the effect of 'labelling' as such, our study provides support for the association between awareness of two different coronary risk factors and incidence of sick leave. Probably a common mechanism is at the base of these findings. Further research is needed, in order to reduce potential negative effects of screening on human wellbeing as well as on productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Research has shown that the attitudes of patients applying for disability pension have an impact on the physician issuing the certificates, which are important for the decision to grant or not to grant disability pensions (12). A study by Leynen et al suggests that there is an increased sickness absence among individuals who are aware of their hypertension (13). We had no information on blood pressure in later life and we were thus unable to confirm whether subjects with hypertension at age 18-19 years still had this condition later in life when applying for a disability pension.…”
Section: Discussionmentioning
confidence: 95%
“…Research has shown that the attitudes of patients applying for disability pension have an impact on the physician issuing the certificates, which are important for the decision to grant or not to grant disability pensions (12). A study by Leynen et al suggests that there is an increased sickness absence among individuals who are aware of their hypertension (13). We had no information on blood pressure in later life and we were thus unable to confirm whether subjects with hypertension at age 18-19 years still had this condition later in life when applying for a disability pension.…”
Section: Discussionmentioning
confidence: 95%
“…Bloom e Monterossa observed that patients who had claimed to be hypertensive, and, however, after a new assessment presented with normal pressure values with no specific treatment, reported more depressive symptoms and worse health perception than normotensive people 27 . Leynen et al observed more missed work days among hypertensive or dyslipidemic individuals who were aware of having these conditions when compared to unaware workers 28 . There was no association between the awareness of a previous AH diagnosis and the occurrence of ITAH in the group of our study population.…”
Section: Discussionmentioning
confidence: 99%
“…9 Our three disease definitions are based on the T-score. We used the distribution of femoral neck bone mineral density in white women ages 20-29 from previous analyses of NHANES III (mean = 0.86 g/cm 2 and standard deviation = 0.12 g/cm 2 ) to calculate a T-score for each woman age fifty and older in our sample. 10 We chose this approach because this reference population has become the most widely used standard.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Simply labeling people as diseased leads to worry and has been shown to make people feel and act sick. 2 Also, as more patients are diagnosed, more are treated, thus exposing them to the potential harms of treatment. Finally, as the number of patients grows, spending rises.…”
mentioning
confidence: 99%